Modern Interpretation of Publicis tic Style and Means of Expressing Its Essence - N. Usmanova (Academia One, 2023)
Political, economic, philosophical and moral problems of society are reflected in publicism, and the subject is real social life - past, present and future tasks.
Keywords: publicist; publicism; journalism